1978
DOI: 10.1097/00006254-197804000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Survival After Severe Birth Asphyxia

Abstract: Thirty-one children who survived severe birth asphyxia defined by a 1-minute Apgar score of 0, or a 5-minute Apgar score of <4, have been seen at age 5 to 10 years for neurological and psychological assessment. Their progress has been compared with that of controls matched for sex, birthweight, gestational age, and social class. 29 (93 %) of the 31 asphyxiated group and all the copyright.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 6 publications
2
19
0
Order By: Relevance
“…However, this study grouped babies with absent heart beat at birth with others who had Apgar scores of between 1 and 4; only 15 babies were given a 1 minute Apgar score of zero and, of these, eight survived; their subsequent neurodevelopmental status is not reported separately. Similar data were reported by Steiner and Neligan,3 and Thompson et al ,4 from severely asphyxiated births between 1964 and 1974. Both neonatal survival and intensive care techniques have changed substantially since then and it seems appropriate to re-evaluate this particular risk group.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, this study grouped babies with absent heart beat at birth with others who had Apgar scores of between 1 and 4; only 15 babies were given a 1 minute Apgar score of zero and, of these, eight survived; their subsequent neurodevelopmental status is not reported separately. Similar data were reported by Steiner and Neligan,3 and Thompson et al ,4 from severely asphyxiated births between 1964 and 1974. Both neonatal survival and intensive care techniques have changed substantially since then and it seems appropriate to re-evaluate this particular risk group.…”
Section: Discussionsupporting
confidence: 88%
“…Combining the outcomes for ascertained children across the three studies, 31 of 72 identified children had severe disability at follow up (43%; 95% CI 31% to 55%). This compares with rates of normal development among survivors of 100%,4 75%,1and 66%3 in the three older studies, which included children with higher Apgar scores.…”
Section: Discussionmentioning
confidence: 87%
“…With advances in neonatal care the outlook for babies surviving severe perinatal asphyxia appears to have improved (Scott, 1976;Thomson et al, 1977), making it more difficult to identify the precise role of asphyxia in causing brain damage. The present study was undertaken in a set of neurologically abnormal babies with a history of fetal distress in labour, to find out whether the types of neurological signs exhibited by such babies have any bearing on their outcome in later infancy or childhood.…”
mentioning
confidence: 99%
“…While there is clearly a relationship between the signs of severe asphyxia and poor prognosis, poor outcomes are not inevitable. There have been reports of newborns with no detectable heartbeats or respiratory effort at birth surviving with normal developmental progress (Scott, 1976;Thomson, Searle, & Russell, 1977). In order to better understand the relationship between asphyxia and developmental outcomes, some investigators have utilized scoring systems to classify infants based on the number and persistence of abnormal neurological signs.…”
Section: Neurological and Developmental Outcomesmentioning
confidence: 99%